2013
DOI: 10.1007/s10654-013-9799-6
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fibre and cardiovascular disease mortality in the UK Women’s Cohort Study

Abstract: Objectives and Background: Dietary fibre has been associated with improvements in key risk factors for cardiovascular disease (CVD). Prior research has focussed more on CVD development in men andour aim was therefore to explore the association between dietary fibre intake and CVD mortality using data from the United Kingdom Women's Cohort Study (UKWCS).Methods and results: Dietary fibre intake from 31,036 women was calculated both as non-starch polysaccharide (NSP) and using the Association of Official Analyti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(72 citation statements)
references
References 45 publications
2
70
0
Order By: Relevance
“…After scrutinising the full-text papers and based on our inclusion criteria, eighteen prospective studies were selected for the systematic review. However, we included only fourteen studies (3)(4)(5)9,10,(12)(13)(14)15,(19)(20)(21)(22)(23) in the meta-analysis, and the other four studies were excluded from the meta-analysis because of the following reasons. Two studies conducted by Rimm et al (24) and Wolk et al (25) were not included because they had reported RR or HR for all CVD events simultaneously and had not separated the findings for fatal and non-fatal outcomes.…”
Section: Excluded Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…After scrutinising the full-text papers and based on our inclusion criteria, eighteen prospective studies were selected for the systematic review. However, we included only fourteen studies (3)(4)(5)9,10,(12)(13)(14)15,(19)(20)(21)(22)(23) in the meta-analysis, and the other four studies were excluded from the meta-analysis because of the following reasons. Two studies conducted by Rimm et al (24) and Wolk et al (25) were not included because they had reported RR or HR for all CVD events simultaneously and had not separated the findings for fatal and non-fatal outcomes.…”
Section: Excluded Studiesmentioning
confidence: 99%
“…The characteristics of the studies included in the systematic review are presented in Table 1. Out of eighteen cohort studies published between 1996 and 2015, ten were conducted in the USA (3)(4)(5)8,10,12,21,(23)(24)(25) , two in the UK (14,19) , two in Australia (15,26) and the rest in Japan (20) , Finland (22) and Netherlands (13) , and one pooled analysis based on cohorts in the USA and UK (9) . The total number of participants in these studies ranged from 1373 (13) to 388 122 (8) , with age ranging from 30 to 99 years.…”
Section: Findings From the Systematic Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Total fibre intake was estimated 63 both as non-starch polysaccharide (NSP) and using the Association of Official Analytical Chemist 64 methods (AOAC) as detailed in a previous study (17). Additionally, soluble fibre, insoluble fibre and 65 fibre from key food sources was estimated as in this previous study.…”
Section: Dietary Assessment 61mentioning
confidence: 99%